Technology-based learning approach and the moderating influence of class size on the Basic Science performance of students - Nwala, Longinus; Nwala, Anthony (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2023)
This study investigates technology-based learning approaches and the moderating influence of class size on the Basic Science performance of junior secondary school students in Etche Local Government Area, Rivers State. A total of 100 JSS 2 students participated in the study. Simple random sampling by balloting to select two UBE schools in Etche and a second round of simple random sampling was carried out to select 100 students from the two schools that partook in the study. There were two classes. One class comprises students in a small class (30 students) while the second class comprises students in a large class (70). The instruments used by the researchers were a well-structured Basic Science Achievement Test (BSAT) and a Student Motivation Questionnaire (SMQ). The instruments underwent content and face validation. Using the Kuder-Richardson (K-R20) method, the BSAT yielded a reliability coefficient of 0.88 whereas with Cronbach Alpha the SMQ yielded an index of 0.77. Both groups received instruction on concepts in Basic Science using mobile technology. Descriptive and inferential statistics, including ANCOVA, were employed for analysis. Results indicate that smaller class sizes significantly enhance student performance, although no significant difference was found between male and female students. While smaller class sizes exhibited slightly higher motivation levels, the difference was not statistically significant. Teachers should actively encourage participation from all students, regardless of the class size and gender, to foster an inclusive learning atmosphere.